Tunable methacrylated decellularized heart matrix: a versatile scaffold for cardiac tissue engineering - Pierre, Valinteshley; Wu, Douglas H.; Liu, Chao; Ertugral, Elif; Kothapalli, Chandrasekhar; Senyo, Samuel E. (Frontiers in Bioengineering and Biotechnology, 2025)
Therapeutic tissue regeneration remains a significant unmet need in heart failure and cardiovascular disease treatment, which are among the leading causes of death globally. Decellularized heart matrix (DHM) offer promising advantages for tissue engineering, including low immunogenicity and seamless integration into biological processes, facilitating biocompatibility. However, DHM is challenged by weak mechanical properties that limit its utility to biomedical applications like tissue engineering. To address this limitation, we functionalized DHM with methacryloyl functional groups (DHMMA) that support UV-induced crosslinking to enhance mechanical properties. By modulating the degree of methacryloyl substitution, a broad range of stiffness was achieved while maintaining cell viability on crosslinked DHMMA. Additionally, we show that increasing UV exposure time and pH increases DHMMA stiffness. Furthermore, topographical features transferred on DHMMA via soft lithography facilitated physical orientation of cells in culture. We demonstrate DHMMA as a scaffold with tunable stiffness and matrix-degradation properties suitable for cell survival and microfabrication for cardiac tissue engineering applications.